IBN SINA about the structure and Types of Logical Reasoning - Oysafar Umarovna, Madjidova (International Journal of Psychosocial Rehabilitation, 2020)
This article is written about the teachings of Ibn Sina on the epistemological and ontological foundations of truth. The number of his writings on questions of logic, metaphysics and psychology exceeded 60. Most of them have been lost, many are just waiting for publication. The deist spiritualist, a student of the Neoplatonists and Aristotle, Avicenna did not give an independent philosophical system. He was interested in abstract questions only to the extent that this was demanded by the currents of Muslim religious thought. The loss of his most important works, which one has to get to know only second-hand, through translators or bad commentators, does not allow an accurate picture of the most important stages of Avicenna’s philosophical life. The article includes analysis and review of available materials, comparative data analysis and conclusions.